Efficient Recruitment of Layer 2/3 Interneurons by Layer 4 Input in Single Columns of Rat Somatosensory Cortex - Helmstaedter, Moritz (J Neurosci, 2008)
Interneurons in layers 2/3 are excited by pyramidal cells within the same layer (Reyes et al., 1998; Gupta et al., 2000), but little is known about translaminar innervation of these interneurons by spiny neurons in the main cortical input layer 4 (L4). Here, we investigated (1) how efficiently L4 spiny neurons excite L2/3 interneurons via monosynaptic connections, (2) whether glutamate release from axon terminals of L4 spiny neurons depends on the identity of the postsynaptic interneuron, and (3) how L4-to-L2/3 interneuron connections compare with L4-to-L2/3 pyramidal neuron connections. We recorded from pairs of L4 spiny neurons and L2/3 interneurons in acute slices of rat barrel cortex of postnatal day 20 (P20) to P29 rats. The L4-to-L2/3 interneuron connections had an average unitary EPSP of 1.2 ± 1.1 mV. We found an average of 2.3 ± 0.8 contacts per connection, and the L4-to-L2/3 interneuron innervation domains were mostly column restricted. Unitary EPSP amplitudes and paired-pulse ratios in the L4-to-L2/3 interneuron connections depended on the “group” of the postsynaptic interneuron. Averaged over all L4-to-L2/3 interneuron connections, unitary EPSP amplitudes were 1.8-fold higher than in the translaminar L4-to-L2/3 pyramidal cell connections. Our results suggest that L4 spiny neurons may more efficiently recruit L2/3 interneurons than L2/3 pyramidal neurons, and that glutamate release from translaminar boutons of L4 spiny neuron axons is target cell specific.